Espiritualidades terapêuticas contemporâneas: seus fundamentos socio-culturais e a construção de uma corporeidade integrativa - Melo, Henrique Arantes de (2014)
This research refers to a socio-anthropological study of contemporary therapeutic spiritualities. After defining a specific circuit composed by the group Meditation Sahaja Yoga, Worshiping place Peregrinos da Luz Divina Pai Benedito and Reiki therapy (Espaço Plenitude and Instituto Seva) it was observed from the sayings and practices that therapeutic spiritualities are part of the New Age phenomenon. Thus, the work has as one of the objectives to list the common elements which are present in the circuit that are consistent with the phenomenon, namely: holistic and vitalistic fundamentals, transcultural and hybrid nature, occidental orientation, psychological, experimentalist and idiosyncratic language, new religious consciousness. Supported by a hermeneutic and phenomenological perspective we attempted to demonstrate how therapeutic spiritualities foster the construction of an integrative corporeality as well as a set of gentle techniques of integrative character. Both integrative corporeality and the study of spiritual techniques were placed in opposition to dualistic corporeality that emerges with modern conceptions of body and instrumental rational perspective of biomedicine, and, to some extent, with the hegemonic representations in official religious circles. We conclude that the phenomenon of therapeutic spiritualities that emerge amid a crisis of institutions that produce meaning collaborate to build new patterns of behavior, new symbolic codes, new sensibilities conforming another somatic culture grounded in holistic and vitalist principles with contra-modern and post-traditional traits.